Penghambatan Penyakit Damping Off (Rebah Semai) pada Semai Pinus dengan Ekstrak Biji Nyiri (Xylocarpus granatum) - Siti Muslimah Widyastuti (Jurnal Perlindungan Tanaman Indonesia, 1996)
Forest Development inIndonesiais based on sustainable concept. To support this policy, forest protection must be done based on environmental approach. In this approach the use of synthetic pesticide must be minimized. Consequently it is necessary to find out alternative method to substitute the use of synthetic pesticide. Phytofungicide is one of the alternative for the synthetic pesticide. The aim of the research was to evaluate the potential of nyiri (Xylocarpus granatum Koen) seed as phytofungicide for controlling Fusarium sp., a pathogen of pine damping off disease. Evaluation was done based on the activity of the extracted nyiri seeds collected from Cilacap mangrove in inhibiting the spore germination and germ tube length in the laboratory, and suppressing the disease intensity in green house. The result showed that the extract of nyiri had antifungal activity against the pathogen tested. This is the first report on the activity of nyiri as phytofungicide for plant pathogens.